2002
DOI: 10.1080/1023697x.2002.10667887
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Seismic Performance of Reinforced Concrete Columns: A Case-study of Hong Kong

Abstract: An experimental study on the improvement of seismIc performance of non-selsmicaiiy designed RC caiumns with varIous configurations of transverse reinforcement is presented. Effects of the configuration of transverse reinforcement on the seismic behaviour and enhancement of ductility are investigated. It has been shown that using the traditionai non-seismic detailing of transverse reinforcement combined with the proposed crosslles can effectiveiy improve the seismic performance, thus enhancing the ductility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As demonstrated by, e.g. Lam et al [16] and Kuang and Wong [17], the deficiencies include poor transverse reinforcement detailing with 90degree hooks and insufficient confinement [16]. It has also been shown that the dependable displacement ductility of this class of columns is highly inadequate.…”
Section: Structural Membersmentioning
confidence: 99%
“…As demonstrated by, e.g. Lam et al [16] and Kuang and Wong [17], the deficiencies include poor transverse reinforcement detailing with 90degree hooks and insufficient confinement [16]. It has also been shown that the dependable displacement ductility of this class of columns is highly inadequate.…”
Section: Structural Membersmentioning
confidence: 99%